Unintended Negative Effects of the Legitimacy-Seeking Behavior of Social Enterprises on Employee Attitudes - Lee, Seung Yun; Shin, Donghoon; Park, Seong Hoon; Kim, Shomi (Frontiers in Psychology, 2018)
In an emerging field such as social enterprise, it is important for an organization to secure legitimacy to obtain resources and sustain its business. Specifically, when a government distributing subsidies does not have adequate information to decide which organization is trustworthy, it is the legitimacy-seeking activities of social enterprise that decides who receives a subsidy; this, in turn, decides which organization will survive. One of the most effective ways to gain legitimacy is to explicitly emphasize in the public promotion that the organization devotes to its social mission. In the case of Work Integration Social Enterprises (WISEs), an organization emphasizes its social employment of the disadvantaged individuals. However, we argue that social enterprises’ public promotion that emphasizes social employment can lower the expected wage, job satisfaction, and organizational commitment of the employees who are hired due to their disadvantaged social status. This is because such obvious promotional messages makes the employees more keenly aware of their disadvantaged status; as a result, this reinforces their self-prejudice that they are not competitive enough in the labor market. We test our hypotheses in the context of South Korean WISEs and found general support for our arguments.